Rule Of Law, Neoliberalisme Dan Proyek Reformasi Hukum World Bank: Perspektif Critical Legal Studies - Anggoro, Syahriza Alkohir (UI Scholars Hub, 2020)
The emergence of World Bank legal reform projects in promoting the rule of law has been successful to encourage third world countries to reform their legal aspects to help formulate market friendly policy. This article tries to question the concept of rule of law that is materialized in many World Bank legal reform projects by using critical legal perspective to analysis legal scholarship on the role of law in the context of development. It trying to present an alternative explanation of World Bank’s rule of law which we are hypothetizing as a neoliberal concept. World Bank’s rule of law are nothing more than a formalistic and limitative concept which is constituted by abstract and universal rules such as protection of private property, contract enforcements and operational efficiency which is a legal framework to easify capitalism. This article conclude that World Bank’s rule of law are bereft of emancipatory values and only serves as a tool for neoliberal penetration to third world countries.